Raising awareness of assistive technology in older adults through a community-based, Cooperative Extension program - Sellers, Debra M.; Markham, Melinda S. (My University, 2012)
The Fashion an Easier Lifestyle with Assistive Technology (FELAT) curriculum was developed as a needs-based, community educational program provided through a state Cooperative Extension Service. The overall goal for participants was to raise awareness of assistive technology. Program evaluation included a post-assessment and subsequent interview to determine short-term knowledge gain and longer-term behavior change. The sample consisted of mainly older, married females. The FELAT program was effective at raising awareness and increasing knowledge of assistive technology, and for many participants, the program acted as a catalyst for planning to or taking action related to assistive technology.
Keywords: Adaptive equipment; Adult education; Curriculum; Disability; Family and consumer sciences